PENDIDIKAN AUD: Berpikir Kritis Berbasis Flip Chart Gambar Seri - Sri Wahyuni; Suyadi Suyadi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Critical thinking is very necessary in today's world, so it must be taught to children from an early age. Critical thinking helps students develop effective problem-solving skills. so that students can analyze problems, identify solutions, and choose the best solution. This study aims to stimulate the critical thinking skills of children aged 4-5 years. The method used is qualitative. The data collection technique used is observation of student behavior when using the flip chart image series media and interviews with teachers and students to find out what they think about the implementation of the media. As well as data analysis techniques in this study are presented in descriptive form sourced from interviews, in this study the subjects of the study were teachers and children. The results of the study showed that the flip chart image series media used can stimulate the critical thinking skills of children aged 4-5 years in solving a problem in the picture series story and are able to provide solutions or opinions related to existing problems. Children are able to understand and recognize information through pictures, children are able to recognize causal relationships through pictures, children are able to evaluate the contents of the story, children are able to provide conclusions related to the contents of the picture series story.